2019
DOI: 10.1051/matecconf/201928103007
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Lebanese polluted waters: a review of current initiatives

Abstract: Water pollution is presently considered as a serious apprehension in Lebanon. Heavy contamination load of nutrients, heavy metals and organic pollutants can be highly harmful for human health and detrimental to aquatic life and ecosystems. Phytoremediation in natural and constructed wetlands using aquatic macrophytes present a sustainable plant-based technology recognized as a very efficient option in water treatment. The employment of species such as Phragmites, Sparganium, Lemna sp and other aquatic macrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The authors of paper [7] showed the problem of water pollution as a serious problem using an example of Lebanon.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The authors of paper [7] showed the problem of water pollution as a serious problem using an example of Lebanon.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Excessive fertilization, particularly nitrogen (N) and phosphorus (P) contaminates soil and water resources [7]. Nitrogen and phosphorus are the main contributors to the eutrophication of freshwaters [8,9]. Eutrophication results in algal blooms that produce harmful toxins such as neurotoxins, hepatotoxins, cytotoxins, dermotoxins and endotoxins, which can have detrimental impacts on humans, animals and the ecosystem [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The term ''phytoremediation'' comes from the Greek word "phyto" = plant, and Latin ''remedium'' = restoring balance. It describes the ability of plants to remove, uptake or stabilize contaminants from soil, water or air [8,10]. Most phytoremediation studies have focused on cleaning contaminated soils, but less attention has been given to purifying polluted water.…”
Section: Introductionmentioning
confidence: 99%